2005
DOI: 10.1016/j.femsec.2004.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Food selection by bacterivorous protists: insight from the analysis of the food vacuole content by means of fluorescence in situ hybridization

Abstract: A modified fluorescence in situ hybridization (FISH) method was used to analyze bacterial prey composition in protistan food vacuoles in both laboratory and natural populations. Under laboratory conditions, we exposed two bacterial strains (affiliated with beta- and gamma-Proteobacteria -- Aeromonas hydrophila and Pseudomonas fluorescens, respectively) to grazing by three protists: the flagellates Bodo saltans and Goniomonas sp., and the ciliate Cyclidium glaucoma. Both flagellate species preferably ingested A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
140
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(153 citation statements)
references
References 39 publications
(106 reference statements)
11
140
1
1
Order By: Relevance
“…5). This observation agrees with previous studies that indicate lower grazing pressure on Actinobacteria by heterotrophic nanoflagellates (18,20) and by the mixotrophic Chrysophyceae Ochromonas sp. (47).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…5). This observation agrees with previous studies that indicate lower grazing pressure on Actinobacteria by heterotrophic nanoflagellates (18,20) and by the mixotrophic Chrysophyceae Ochromonas sp. (47).…”
Section: Discussionsupporting
confidence: 93%
“…Prey identification can be addressed by techniques based on DNA fingerprinting (15,16), which allow ensuing taxonomic changes in prey assemblages (10,17). Linking prey and predator can be addressed using techniques based on fluorescence in situ hybridization (FISH), which allow detecting targeted prey inside protist food vacuoles (5,14,18,19). These techniques have been performed mostly under experimental conditions (18,20), and results suggest a high selectivity in the feeding of heterotrophic flagellates and some ciliate species investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, each species might have different prey preferences, being adapted to consume a specific part of the bacterial assemblage. The most critical parameter to define the grazing vulnerability of a given bacteria is its cell size (González et al, 1990), but other factors such as cell viability (Landry et al, 1991), surface properties (Matz and Jü rgens, 2001), motility (Matz and Jü rgens, 2005), phylogenetic affiliation (Jezbera et al, 2005) or food quality (Shannon et al, 2007) have been also demonstrated. Finally, intrinsic physiological parameters like the functional response (relationship of grazing rates with prey concentration) or the growth efficiency (conversion of ingested food to biomass) might explain adaptations to specific environmental settings.…”
Section: Introductionmentioning
confidence: 99%
“…Giving an insight into protozoan communities is hereby of great significance in expanding the holistic understanding of activated-sludge ecosystem, and thus improving the performance of the existing biological treatment processes. It is accepted that the protozoan communities will be influenced in two pathways: to be manipulated directly by virtue of their inherent sensitivities to environment, and meanwhile to be modified indirectly in accordance with the potential changes of bacterial community structures through food chain (Curds and Cockburn, 1970;Zarda et al, 1998;Jezbera et al, 2005;Nicolau et al, 2005). For building the species-habitat relationship, most previous studies have been devoted to monitoring protozoan communities for predicting effluent quality and plant performance (Curds and Cockburn, 1970;Poole, 1984;Al-Shahwani and Horan, 1991;Salvadó et al, 1995;Martín-Cereceda et al, 1996).The species of protozoa present in activated sludge have been well inventoried as important bio-indicators since last century (Curds and Cockburn, 1970;Madoni and Ghetti, 1981;Madoni et al, 1993;Nicolau et al, 2001).…”
Section: Introductionmentioning
confidence: 99%